A Simple Numerical Modeling of the Effect of the Incoherent Thick Substrate in Thin-Film Solar Cells Based on the Equispaced Thickness Method - Kyungnam Kang; Sanghwa Lee; Jungho Kim; Sungchul Kim; Younho Han; Seungin Baek (IEEE Photonics Journal, 2016)
We propose a simple numerical modeling method to consider the effect of the incoherent thick substrate on the absorption characteristics of thin-film solar cells. In the proposed “equispaced thickness method” (ETM), the incoherent optical characteristics of the thick substrate are modeled by adding an additional thickness that gives an equispaced phase shift to the incoherent substrate and averaging the coherent simulation results over several equispaced thicknesses. The proposed ETM can be used to consider the effect of the incoherent glass substrate without complicated mathematical and computational procedures and is applicable to not only planar but also surface-textured thin-film solar cells. By applying the proposed method to the numerical modeling based on the finite element method (FEM), we calculate the reflectance spectra in planar and surface-textured thin-film solar cells, respectively. The simulation condition of the FEM, such as mesh size, is determined to match the numerical results based on the ETM with the analytical results obtained by the generalized transfer matrix method. For comparison, the reflectance spectra in the same structures are calculated by taking the average over coherent calculation results for a large number of random thicknesses of the incoherent layer. According to the comparison of the calculated statistical deviations from the exact solution between the ETM and the random thickness method, the ETM reduces the number of simulations by at least a factor of 50 with the same accuracy.